جودة نظم المعلومات المحاسبية المؤتمتة في الشركات الصناعية في الساحل السوري - محمد نذير (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف هذا البحث إلى التأكد من جودة نظم المعلومات المحاسبية في الشركات الصناعية، ولتحقيق هذا الهدف تم تصميم استبانة وزعت على عينة من تلك الشركات العاملة في الساحل السوري. ومن خلال تحليل البيانات التي تم جمعها واختبار فرضيات الدراسة تم التوصل إلى مجموعة من النتائج منها: عدم وجود ثقافة كافية فيما يخص نظم المعلومات المحاسبية، وعدم توافر البنية التحتية لتكنولوجيا إضافة إلى ضعف أنظمة الرقابة الداخلية وإجراءات الأمان. وقد أوصت الدراسة: بضرورة البحث في الفوائد التي يعود فيها استخدام نظم المعلومات المحاسبية على المنشآت لتتمكن هذه المنشآت من الاستفادة من تفعيله فيها بالشكل الأمثل والعمل على اجراء البحوث اللازمة لمعرفة مدى توافق البنى التحتية للمنشآت التي تتعامل مع نظم المعلومات المحاسبية والعمل على تحسينها واقتراح الحلول المناسبة لتتمكن المنشآت من تفعيله بشكل إيجابي. This research aims to ensure the quality of accounting information systems in industrial companies. To achieve this goal, a designed questionnaire was distributed to a sample of employee working at some Syrian coast companies. Based on proper hypotheses, the analytical data showed a set of conclusions. These include: the lack of adequate culture with respect to accounting information systems, the lack of IT infrastructure, in addition to the weakness of internal controls and the procedures of security systems. The study recommended the need to take advantage of the use of accounting information systems at the enterprises to enable them to benefit these systems optimally. Moreover, it is worthwhile to do more research in order to know the extent of infrastructure compatibility of the companies that deal with accounting information systems in order to improve it and to propose appropriate solutions to enable enterprises to be activated positively.